Primary cardioprotection with dexrazoxane in patients with childhood cancer who are expected to receive anthracyclines: recommendations from the International Late Effects of Childhood Cancer Guideline Harmonization Group. (December 2022) - de Baat, Esmée C; van Dalen, Elvira C; Mulder, Renée L; Hudson, Melissa M; Ehrhardt, Matthew J; Engels, Frederike K; Feijen, Elizabeth A M; Grotenhuis, Heynric B; Leerink, Jan M; Kapusta, Livia; Kaspers, Gertjan J L; Merkx, Remy; et al.
Summary: Survivors of childhood cancer are at risk of anthracycline-induced cardiotoxicity, which might be prevented by dexrazoxane. However, concerns exist about the safety of dexrazoxane, and little guidance is available on its use in children. To facilitate global consensus, a working group within the International Late Effects of Childhood Cancer Guideline Harmonization Group reviewed the existing literature and used evidence-based methodology to develop a guideline for dexrazoxane administration in children with cancer who are expected to receive anthracyclines. Recommendations were made in consideration of evidence supporting the balance of potential benefits and harms, and clinical judgement by the expert panel. Given the dose-dependent risk of anthracycline-induced cardiotoxicity, we concluded that the benefits of dexrazoxane probably outweigh the risk of subsequent neoplasms when the cumulative doxorubicin or equivalent dose is at least 250 mg/m 2 (moderate recommendation). No recommendation could be formulated for cumulative doxorubicin or equivalent doses of lower than 250 mg/m 2, due to insufficient evidence to determine whether the risk of cardiotoxicity outweighs the possible risk of subsequent neoplasms. Further research is encouraged to determine the long-term efficacy and safety of dexrazoxane in children with cancer.